Usborne illustrated pirate stories - Broadley, Leo (Usborne London, 2014)
"Landlubbers beware! This book is bristling with swashbuckling sea dogs, cursed cabin boys and zombie pirates. Expect nail-biting danger, booming cannons, treasure and plenty of parrots." -- Page [4] cover